Peer-to-peer media streaming with HTML5 - Ali Tariq Kalil Al-Khayyat; Sanabil A. Mahmood (International Journal of Electrical and Computer Engineering (IJECE), 2023)
The knowledge of web real-time communication (WebRTC) and how its customers and server operations are defined in this study. However, the world wide web consortium (W3C) and the internet engineering task force (IETF) have not yet approved an absolute signaling protocol or a complete application programming interface (API) protocol to implement WebRTC and control communication planning. WebRTC requires some type of signaling mechanism. With Chrome, Firefox, and Opera, the primary objective is to create and implement a WebRTC video call across two clients (peers) in the real world while employing local area network (LAN) and wide area network (WAN). This study also demonstrated the design of the server (as an intermediary) and graphical user interface (GUI). Additionally, a signaling method for the peer-to-peer browser connection on the Node.js platform has been developed and successfully put into use. This paper will provide an understanding of web development and an ability to understand WebRTC technology. It will also discuss how to create WebRTC signaling mechanisms and build video conferencing, as well as how to increase design quality using quality of experience (QoE) techniques.